Correction of Intestinal Dysbiosis in Primary School-aged Children During Rehabilitation after Infectious Gastroenteritis Using Lactovit Forte - L.V. Kvashnina; V.P. Rodionov (Zaslavsky O.Yu., 2012)
The article presents data on the use of spore-forming probiotics (Lactovit Forte) for the correction of intestinal dysbiosis in the recovery period after acute gastroenterocolitis in primary school-aged children.